[Autofluorescent cells in the sacculus rotundus in the rabbit] - Aita, M; Pezzella, F; Minella, AB; Amantea, A (1978)
Many autofluorescent cells, rich in yellow pigment are described in the rabbit's sacculus rotundus. This pigment stained positively with Sudan black, PAS and Masson-Hamperl techniques. The cells correspond to those described in rat and in mice lymphatic organs. The possible origin of the pigment is discussed.